Oral health impacts profile of Malaysian adults in Nohsa 2010 - S, Zainab; R, Saub; SL, Yaub; AM, Khairiyah; Ab Rahman, Jamalludin (2014)

(untitled)
Objective: In NOHSA 2010, a modified cross culturally adapted standardized socio dental questionnaire, the Malay short version Oral Health Impact Profile(S-OHIP[M]) was used to assess the impact of oral health on the quality of life of Malaysian adult. Methodology: A total of 9,065 Malaysian adults aged 15 years and above participated in the survey. Participants were interviewed using the S-OHIP[M]) questionnaire prior to mouth examination. The questionnaire consists of 16 items covering 7 domains of the oral health impacts namely, oral functional limitation, psychological discomfort, physical pain, psychological disability, physical disability, social disability and handicap. The five point frequency Likert Scale was used as the response format. An impact was defined as having experienced of at least one impact reported either "very often" or "often" due to oral condition(s) iil the last three months preceeding the survey. Severity of impact is the sum of 16 items response options. Total score ranges from 0 to 64. Higher score indicates higher impact. The prevalence and severity of impact was analysed using SPSS version 17. Results: Overall29.3% (95%CI:27.8-30.80) of Malaysian adults reported some form of impact due to oral health problems. Feeling uncomfortable due to food getting stuck in between teeth or dentures [20.0% (95%CI:18.8-21.2)] was the most common impact reported, followed by avoiding-- -certain- --food [S%(95%CI:7.3-8.8)], difficulty in chewing [6.2%[9S%CI:5.6-6.9)] and bad breadth [5.4%(95%CI:5.6-6.9)]. A higher prevalence of impact was noted among adults with 1-19 teeth [32.9% [95%CI:30.1-35.8)] compared to edentulous adults [21.6% [95%CI:18.2-25.4)]. The mean S-OHIP[M] score is 5.87(95%CI:5.63-6.11). Conclusion: About 3 in 10 Malaysian adults experienced one or more impact from oral condition{s). The most common impact was discomfort while eating. Dentition status, caries status and periodontal status had significant relationship with impact measures. Prevalence and severity of impacts wa·s found to- -be significantly associated with self-perception and satisfaction towards oral health.